(untitled) (Journal of Science and Technology, 2016)
Seeds of five different landrace cultivars of Kersting’s groundnut, Macrotyloma geocarpum(Harms) Marechal and Baudet, obtained from northern Ghana, were evaluated for their susceptibility to infestation and damage by the pulse beetle, Callosobruchus maculatus Fab. The completely randomized design was used to obtain data on the oviposition, developmental period, progeny emergence, weight loss in seeds and susceptibility index. The results showed that the Nakpanduri-white, Heng-mottle and Damongo-cream landrace cultivars proved to be the highly preferred hosts to C. maculatus, recording the highest egg load and progeny emergence, as well as the shortest egg-adult developmental period, and highest seed weight loss. The Najung-black landrace cultivar was the least preferred, followed by the Nakori-brown cultivars. Results from susceptibility indices further indicated that the Najung-black and Nakori-brown were the least susceptible to C. maculatus, while Nakpanduri-white was the most susceptible. Overall, the Najung-black and Nakori-brown landrace cultivars consistently demonstrated high tolerance to the pest and therefore, should be promoted or incorporated into breeding programmes to help minimize the high losses incurred by farmers during storage.